PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI, KEAHLIAN PEMAKAI, DAN INTENSITAS PEMAKAIAN TERHADAP KUALITAS INFORMASI AKUNTANSI (Studi Pada Satuan Kerja Perangkat Daerah Kabupaten Indragiri Hulu) - Nova Evania; Taufeni Taufik; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to the effect of information technology use, user expertise, and intensity of usage affect the quality of accounting information. Populations in this study is a subsection of finance, treasurer, manager of the accounting department, and finance staff that work on the unit of work in the SKPD Kab. Indragiri Hulu. The sampling technique using purpose sampling. Total respondents in this research are 60 respondent. The data of this research using primary data directly through a questionnaire and analyzed using SPSS 17. The data were analyzed to test the hypothesis using multiple linear regression analysis approach.The result of this study indicates that information technology use a significant to quality of accounting information with regression coefficient 0,575 and significant value 0,000 (alpha 0,05), this is shown by the result of tcount> ttable that is 4,201 > 2,009. User expertise a significant to quality of accounting information with regression coefficient 0,322 and significant value 0,035 (alpha 0,05), this is shown by the result of tcount> ttable that is 2,173 > 2,009. Where as the intensity of usage does not effect the quality of accounting informationwith regression coefficient 0,254 and significant value 0,332 (alpha 0,05), this is shown by the result of tcount< ttable that is 0,980 < 2,009. Based on the calculation of the coefficient of determination (Adjusted R²) obtained a value of 0,518. This shows that the influence of the independent variables in the dependent 51,8% and the remaining 48,2% influenced by other variables.Keywords : quality of accounting information, information technology use, user expertise, and intensity of usege